Crop rotation reduces the frequency of anaerobic soil bacteria in Red Latosol of Brazil - Cezar, Raul Matias; Vezzani, Fabiane Machado; Kaschuk, Glaciela; Balsanelli, Eduardo; de Souza, Emanuel Maltempi; Vargas, Luciano Kayser; Molin, Rudimar (Brazilian journal of microbiology, 2021)
Crop diversity affects the processes of soil physical structuring and most likely provokes changes in the frequencies of soil microbial communities. The study was conducted for soil prokaryotic diversity sequencing 16S rDNA genes from a 25-year no-tillage experiment comprised of two crop systems: crop succession ( Triticum aestivum - Glycine max ) and rotation ( Vicia sativa - Zea mays - Avena sativa - Glycine max - Triticum aestivum - Glycine max ). The hypothesis was that a crop system with higher crop diversification (rotation) would affect the frequencies of prokaryotic taxa against a less diverse crop system (succession) altering the major soil functions guided by bacterial diversity. Soils in both crop systems were dominated by Proteobacteria (31%), Acidobacteria (23%), Actinobacteria (10%), and Gemmatimonadetes (7.2%), among other common copiotrophic soil bacteria. Crop systems did not affect the richness and diversity indexes of soil bacteria and soil archaea. However, the crop rotation system reduced only the frequencies of anaerobic metabolism bacteria Chloroacidobacteria , Holophagae , Spirochaetes , Euryarchaeota , and Crenarchaeota. It can be concluded that crop succession, a system that is poorer in root diversity over time, may have conditioned the soil to lower oxygen diffusion and built up ecological niches that suitable for anaerobic bacteria tolerating lower levels of oxygen. On the other hand, it appeared that crop rotation has restructured the soil over the years while enabling copiotrophic aerobic bacteria to dominate the soil ecosystem. The changes prompted by crop succession have implications for efficient soil organic matter decomposition, reduced greenhouse gas emissions, higher root activity, and overall soil productivity, which compromise to agriculture sustainability.